Convection in ferro-nanofluids : experiments and theory : physical mechanisms, flow patterns, and heat transfer /: experiments and theory : physical mechanisms, flow patterns, and heat transfer. ([2018]) - Bozhko, Aleksandra A; Suslov, Sergey A
No abstract available